Assume y varies inversely as x, how do you write the equation given y=-6 when x=-3?

2 Answers
May 29, 2017

yprop(1/x)

so, y = k/x

With x = -3 and y = -6 we have:

-6 = k/-3

=> k = 18

Then, y = 18/x

or, xy = 18

:)>

May 29, 2017

y = 18/x

Explanation:

This sounds like inverse proportionality.

The standard writing for such a formula is: y = k/x

Given the information, y = -6 when x =-3, we can find the constant "k".
-6 = k/-3 iff k = -6*(-3)=18

Now we know "k", we write the formula that sitifies y = -6 when x = -3 as y = 18/x